Capillary zone electrophoresis as alternative tool for rapid identification and quantification of viable Saccharomyces cerevisiae cells. (May 2016) - Crispo, Fabiana; Capece, Angela; Guerrieri, Antonio; Romano, Patrizia
Abstract: The aim of this work was to evaluate the possibility of using capillary electrophoresis for rapid and sensitive detection of microorganisms, such as yeasts, in order to propose it as an alternative to traditional microbiology methods both in manufacturing and research areas. After optimization of condition for the electrophoretic separation, three Saccharomyces cerevisiae strains, cultured in YPD medium, were analyzed by capillary electrophoresis at different growth times (3, 7, 24 and 48 h). The analysis was carried out on undamaged and non-pretreated cells. For all the strains, the electrophoretic profile was characterised by two distinct peaks, at each time of growth. Nevertheless some differences in the electropherograms of each strain were evident, probably in consequence of changing in the surface charge of yeasts at various stage of growth. The results demonstrated the high efficacy of capillary electrophoresis for intact cells separation of yeast and support the application of this technique for the evaluation of the viability of cultured cells. Highlights: Conditions for efficiently separation of living Saccharomyces cerevisiae by capillary zone electrophoresis were optimized. Electrophoretic profile of viable S. cerevisiae cells is characterized by two peaks. A correlation between S. cerevisiae electrophoretic profile and cells viability was found. Capillary zone electrophoresis as alternative methods for high-efficiency detection of S. cerevisiae .